Epidemiology of rabies immune globulin use in paediatric and adult patients in the USA: a cross-sectional prevalence study. Issue 4 (26th April 2022) - Burke, Rita V; Russo, Pierantonio; Sicilia, Michael; Wolowich, William; Amega, Novinyo; Nguyen, Huy-Binh
Abstract : Objectives: To compare the epidemiology of paediatric and adult patients receiving rabies immune globulin (RIG). Design: Cross-sectional prevalence study. Setting: Eligible participants from the Symphony Integrated Dataverse presenting between 2013 and 2019. Participants: All adult and paediatric patients with integrated claims and demographic data associated with RIG use from the Symphony Integrated Dataverse from 2013 to 2019. Primary and secondary outcome measures: Prevalence of diagnoses and procedures associated with paediatric and adult patient population based on frequency of International Classification of Diseases (ICD-9/ICD-10) and Current Procedural Terminology codes, respectively. Methods: We used mutual information to identify features that differentiate the paediatric from adult patient population. Prevalence ratios were calculated to compare adult and paediatric patients. Results: There were 79 766 adult and 20 381 paediatric patients who met the inclusion criteria. Paediatric patients had a 5.92-fold higher prevalence of 'open wounds to the head; neck; and trunk', 3.10-fold higher prevalence of 'abrasion or friction burn of face; neck; and scalp except eye; without mention of infection', 4.44-fold higher prevalence of 'open wound of scalp; without mention of complication' and 6.75-fold higher prevalence of 'laceration of skin of eyelid and periocular area | laceration of eyelid involving lacrimal passages'. Paediatric patients had a 3.83-fold higher prevalence of complex repairs compared with adult patients (n=157, 0.7% vs n=157, 0.2%, respectively). Conclusions: Paediatric patients represent a significant proportion of the patient population receiving RIG, and are associated with higher prevalence of codes reporting repair of larger, more complex wounds in highly innervated anatomical regions. Dosing and administration of RIG must be informed by animal bite wound characteristics; clinicians should understand the differences between presentations in adults and children and treat accordingly.